PENDAMPINGAN PROSES PENYUSUNAN APBDES TA-2025: DESA PARHABINSARAN JANJIMATOGU KECAMATAN ULUAN KABUPATEN TOBA (Jurnal Akuntansi, 2026)
Village development is an important pillar of Indonesia’s national development, where Village Funds provide opportunities for villages to plan development according to local needs. However, Parhabinsaran Janjimatogu Village, Uluan District, Toba Regency, still faces challenges in preparing the Village Revenue and Expenditure Budget (APBDes) due to limited capacity of village officials, both in terms of regulatory understanding, administrative skills, and technological proficiency. This study was conducted to analyze the obstacles and provide recommendations to improve the effectiveness of APBDes preparation through strengthening the capacity of village officials. The research method employed a participatory and collaborative approach, involving village government, Village Consultative Body (BPD), community leaders, and other local stakeholders. The results show that the use of the Village Financial System Application (SISKEUDES) can enhance the capacity of village officials in managing and preparing APBDes in a more accountable and transparent manner. The challenges identified include limited technical understanding of the application, inadequate supporting facilities, and weak coordination among village officials. This study is expected to contribute positively to strengthening the capacity of village officials in utilizing SISKEUDES for APBDes preparation, as well as providing recommendations to reinforce inter-institutional cooperation in order to improve community welfare.​